Regional Regulation Implementation of Madiun City Number 45 of 2018 Concerning with Prevention and Enhancement of Slum Housing and Settlement Quality - Sarjiyati Sarjiyati; Sigit Sapto Nugroho; Anggun Enggar Pratiwi (Faculty of Law, Universitas Sebelas Maret, 2020)
The purpose of this study was to determine and analyze the implementation of the Regional Regulation of Madiun City Number 45 of 2018 concerning with Prevention and Improvement of Quality of Housing and Slums and the constraints in the implementation of the City without Slums Program in Madiun City. This research method uses empirical data that is obtained directly through field research with primary, secondary and tertiary data sources as well as data collection by observation, interview, document study analyzed descriptive qualitative. The results of this study indicate that the Government of Madiun City has implemented Regional Regulation Number 45 of 2018 regarding Prevention and Improvement of Quality of Housing and Slums, quite well, there are 6 (six) villages which are categorized in mild slum areas. There are inertnal and external constraints in the implementation of the Cityless Slums Program in Madiun City.